Addressing financial mismanagement in state-owned enterprises and municipalities: An integrative review and call for action - Charmaine, Moyo Kearabilwe; Nwosu, Lilian Ifunanya; Enwereji, Prince Chukwuneme; Ogundele, Omobolade Stephen (Edelweiss Applied Science and Technology, 2024)
This study critically explored the financial measures and policies that can be implemented to protect and mitigate the risks of mismanagement of the financial resources of state-owned enterprises (SOEs) and municipalities. This study adopted a qualitative research approach by reviewing readily available literature such as books, journals, articles, and other published materials. A stakeholder theoretical framework was used to understand the organisational ethics, morality, and values of SOEs and municipalities and their interactions and relationships with public and private firms and South African citizens. The significant findings of the study revealed that factors such as corruption, lack of financial transparency, and inadequate governance structures contribute to the mismanagement of funds in SOEs and municipalities. The findings further highlighted the urgent need to address the mismanagement of funds in SOEs and municipalities. The study calls for urgent action to strengthen financial accountability and oversight mechanisms and implement effective measures to combat corruption. By addressing these issues, SOEs and municipalities facing these challenges can promote financial integrity, restore public trust, and ensure the efficient use of public resources. The study recommended that SOEs should be protected from economic mismanagement, embezzlement, state capture, and corruption, requiring the implementation of effective financial measures.